Assessment of intermolecular interaction of mefenamic acid (Form II) in acetone and dimethylformamide (DMF) solution using molecular modelling technique / Nur Syazwina Mohd Aizuddin ... [et al.] - Mohd Aizuddin, Nur Syazwina; Supian, Muhammad Syahir Syazwan; Shahrir, Nurshahzanani; Anuar, Nornizar (Universiti Teknologi MARA Shah Alam, 2023)
Solvent plays an important role in the solute-solvent intermolecular interactions of crystal morphology to regulate the crystal shape. Therefore, this work aims to assess the role of functional groups of solvents on the preferential sites on mefenamic acid (Form II) crystal surfaces, namely {001}, {011}, and {010} using the computational molecular modelling interactions techniques. The crystal morphology was successfully predicted as a plate-like crystal morphology using the BFDH method, and the molecular interactions of solute-solvent were assessed using the surface-docking method via Biovia Materials Studio software. The solute and solvent interactions along with surfaces used in this study disclosed that the {001} surfaces had the most negative non-bonded energy, followed by the {010} and {011} surfaces, ranging from −2036 to −2994 kcal/mol. Meanwhile, the binding energy values of acetone on all facets of interest were stronger compared to the binding energy of DMF, which possessed the binding energy of only less than −10 kcal/mol. Nevertheless, the results showed that acetone as a small molecule interacted most strongly with all facets of mefenamic acid (Form II) crystals because it could form stronger hydrogen bonds due to its ketone functional group, hence inhibited the growth of the mefenamic acid (Form II) crystal facets.